2015
DOI: 10.2147/ov.s66086
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virotherapy using herpes simplex virus: how far have we come?

Abstract: Oncolytic virotherapy exploits the properties of human viruses to naturally cytolysis of cancer cells. The human pathogen herpes simplex virus (HSV) has proven particularly amenable for use in oncolytic virotherapy. The relative safety of HSV coupled with extensive knowledge on how HSV interacts with the host has provided a platform for manipulating HSV to enhance the targeting and killing of human cancer cells. This has culminated in the approval of talimogene laherparepvec for the treatment of melanoma. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 137 publications
0
16
0
Order By: Relevance
“…This includes but is not limited to, actin remodelling during viral surfing prior to entry (and most likely exit), transport along microtubules to deliver viral components to and from the nucleus and for axonal transport during initial viral uptake into the sites of latency or reactivation. Certainly, in the context of cytoskeleton regulation and subversion of molecular motors by alphaherpesviruses our increasing knowledge will not only provide targets for new antivirals but inform on attenuated virus design for gene therapy [ 191 ], oncolytic virotherapy [ 27 ] and vaccine development [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes but is not limited to, actin remodelling during viral surfing prior to entry (and most likely exit), transport along microtubules to deliver viral components to and from the nucleus and for axonal transport during initial viral uptake into the sites of latency or reactivation. Certainly, in the context of cytoskeleton regulation and subversion of molecular motors by alphaherpesviruses our increasing knowledge will not only provide targets for new antivirals but inform on attenuated virus design for gene therapy [ 191 ], oncolytic virotherapy [ 27 ] and vaccine development [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current antivirals target DNA replication during the viral lifecycle but new mechanisms and the advent of combination therapies may lead to better patient outcomes. Furthermore, HSV has been targeted for use as a viable gene therapy vehicle and is used in the field of oncolytic virotherapy for the treatment of solid tumours [ 27 , 28 ]. Therefore, further investigation of the crucial virus-host interactions involved during the lifecycles of these alphaherpesviruses will pull the cytoskeletons from the closet; the discovery of these unknown mechanisms will benefit the understanding of alphaherpesvirus reactivation pathways and potentially lead to novel therapeutic options.…”
Section: Herpesvirusesmentioning
confidence: 99%
“… 40 These viruses have a large genome that is amenable to genetic manipulation and the insertion of therapeutic genes, making them an attractive platform for the development of novel virus-based therapies. Several distinct oHSVs have been engineered by investigators and pharmaceutical companies, 41 – 45 including the recently FDA-approved oHSV talimogene laherparepvec (T-VEC) for the treatment of melanoma. 46 Multiple preclinical and early-phase clinical trials have shown that combining these agents with PD-1/PD-L1 blockade can be beneficial.…”
Section: Combination Of Oncolytic Dna Viruses With Pd-1/pd-l1 Checkpomentioning
confidence: 99%
“…HSV-1, belonging to family Herpesviridae of neurotropic dsDNA viruses, is a causative agent of a self-limiting disease. Due to its cytolytic replication cycle and easily modified large genome, HSV-1 is beneficial as an oncolytic agent [ 62 , 63 ]. Moreover, HSV-1 infects different cell types, and the presence of a separate attachment and fusion glycoproteins within its envelope is beneficial for modification to improve tumor targeting [ 63 ].…”
Section: Ovs and Nf-κbmentioning
confidence: 99%